Facial Structure Is a Reliable Cue of Aggressive Behavior - Carré, Justin M.; McCormick, Cheryl M.; Mondloch, Catherine J. (Psychological Science, 2009)
Facial width-to-height ratio is a sexually dimorphic metric that is independent of body size and may have been shaped by sexual selection. We recently showed that this metric is correlated with behavioral aggression in men. In Study 1, observers estimated the propensity for aggression of men photographed displaying neutral facial expressions and for whom a behavioral measure of aggression was obtained. The estimates were correlated strongly with the facial width-to-height ratio of the stimulus faces and with the actual aggression of the men. These results were replicated in Study 2, in which the exposure to each stimulus face was shortened to 39 ms. Participants' estimates of aggression for each stimulus face were highly correlated between Study 2 (39-ms exposure) and Study 1 (2,000-ms exposure). These findings suggest that the facial width-to-height ratio may be a cue used to predict propensity for aggression in others.